2023
DOI: 10.3390/jof9020170
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Application of the Non-Conventional Yeast Pichia kudriavzevii in Food and Biotechnology Industries

Abstract: Pichia kudriavzevii is an emerging non-conventional yeast which has attracted increased attention for its application in food and biotechnology areas. It is widespread in various habitats and often occurs in the spontaneous fermentation process of traditional fermented foods and beverages. The contributions of P. kudriavzevii in degrading organic acid, releasing various hydrolase and flavor compounds, and displaying probiotic properties make it a promising starter culture in the food and feed industry. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 158 publications
0
7
0
Order By: Relevance
“…The three yeast species identified in this study (P. kudriavzevii, R. mucilaginosa, and C. tropicalis) have also been reported in the ruminal microbiota analysis of cattle fed with tropical forages (Abrão et al 2014, Fernandes et al 2019). The species detected most frequently in the present study was P. kudriavzevii, which is an ambiguous species present in natural environments and occurs in traditionally fermented foods and drinks on different continents, contributing to the production of flavor compounds and exhibits probiotic properties (Chu et al 2023;Ganapathiwar et al 2023). This yeast has a high tolerance to ethanol, pH, high temperature, hyperosmotic stress and lignocellulosic inhibitors, which are notable characteristics for industrial applications (Mukherjee et al 2017).…”
Section: Discussionmentioning
confidence: 76%
“…The three yeast species identified in this study (P. kudriavzevii, R. mucilaginosa, and C. tropicalis) have also been reported in the ruminal microbiota analysis of cattle fed with tropical forages (Abrão et al 2014, Fernandes et al 2019). The species detected most frequently in the present study was P. kudriavzevii, which is an ambiguous species present in natural environments and occurs in traditionally fermented foods and drinks on different continents, contributing to the production of flavor compounds and exhibits probiotic properties (Chu et al 2023;Ganapathiwar et al 2023). This yeast has a high tolerance to ethanol, pH, high temperature, hyperosmotic stress and lignocellulosic inhibitors, which are notable characteristics for industrial applications (Mukherjee et al 2017).…”
Section: Discussionmentioning
confidence: 76%
“…The studies showed that P . kudriavzevii has high fermentation performance characteristics, such as potential enzymatic activities, high tolerance to diverse stresses, and crucial production of desirable metabolite profiles (Chu et al, 2023; Haile & Kang, 2019; Krajangsang et al, 2022; Shankar et al, 2022). Other yeast species, such as P .…”
Section: Discussionmentioning
confidence: 99%
“…Yeast extracts are rich in aroma compounds and hence much used commercially as flavoring agents in many kinds of food. In addition, the yeast species P. kudriavzevii is also explored for natural production of aroma compounds (Dan et al., 2020 ; Yunfei et al., 2023 ), for instance, in sourdough bread together with Lactobacillus plantarum . Our focus was on nutritional enhancement and not on sensory properties.…”
Section: Discussionmentioning
confidence: 99%
“…One such nonconventional yeast, Pichia kudriavzevii TY13, with a high capacity to synthesize and release phytase to the surrounding medium was recently isolated from a Tanzanian lactic acid fermented maize gruel (togwa) (Hellström et al, 2010(Hellström et al, , 2015. The species P. kudriavzevii is ubiquitous in nature and very common in traditional fermented foods in all parts of the world (Yunfei et al, 2023). It is currently being explored for its potential in food production, as probiotic and in biotechnology, for instance, known to contribute to a pleasant aroma profile in, for example, wine and sourdough bread (Dan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%